Agency Cost of Debt and Lending Market Competition: Is there a Relationship? - Erkki Koskela; Rune Stenbacka (Center for Economic Studies and ifo Institute (CESifo), 2000)
We address the question of how lending market competition, measured by the bargaining power of banks, affects the agency costs of debt finance. It is shown that intensified lending market competition will lead to lower lending rates and investment return distributions which are shifted towards lower, but less risky returns. Consequently, it follows that increased lending market competition will reduce the agency cost of debt financing. Hence, our analysis does not lend support to the commonly held view that there would be a trade-off between more intensive lending market competition and higher agency costs of debt finance.
Keywords: 330; Bank competition; agency cost of debt